Antioxidant capacity, cytotoxicity and antimycobacterial activity of Madeira Archipelago endemic helichrysum dietary and medicinal plants - Gouveia-Figueira, Sandra C. (2014)
The potential bioactivity of dietary and medicinal endemic Helichrysum plants from Madeira Archipelago was explored, for the first time, in order to supply new information for the general consumer. In vitro antioxidant properties were investigated using DPPH, ABTS(•+), FRAP and β-Carotene assays, and the total phenolic content (TPC) and total flavonoid content (TFC) were also determined. Although the results generally showed a large variation among the three analyzed plants, the methanolic extracts showed the highest antioxidant capacity. Exception is made for H. devium n-hexane extract that showed good radical scavenger capacity associated to compounds with good reducing properties. In the Artemia salina toxicity assay and antimycobaterial activity, H. devium was the most potent plant with the lowest LD50 at 216.7 ± 10.4 and MIC ≤ 50 μg·mL(-1). Chemometric evaluation (Principal Component Analysis-PCA) showed close interdependence between the ABTS, TPC and TFC methods and allowed to group H. devium samples.